Diagnosic and treatment of a persistent fourth right aortic arch in a dog - Chipayo G., Ysaac (2019)
The persistent of the aortic right arch is a congenital anomaly that is considered difficult to treat in Peru, and therefore is presented the case of a three-month-old Cocker Spaniel canine with a history of chronic regurgitation of solid foods and poor development. At clinical examination he was alert and active but with low body condition; the esophagus on palpation at the cervical level was apparently flaccid and noticeable, and at abdominal compression it seemed to increase its volume. The contrasted radiographic image revealed a marked esophageal distension located in front of the cardiac image, which gave the diagnosis of a pre-cardiac megaesophagus. The presumptive diagnosis was the presence of the fourth persistent right aortic arch, so the surgery was suggested to the owners. Exploratory thoracic surgery was performed confirming the diagnosis and corrective surgery was performed by ligand and transecting the fourth persistent aortic arch. A rapid recovery was observed in the patient, and monthly evaluations for a year were done without detecting complications.